Current-induced magnetization switching in Pt/Co/Ta with interfacial decoration by insertion of Cr to enhance perpendicular magnetic anisotropy and spin–orbit torques. (29th November 2017) - Cui, Baoshan; Chen, Shiwei; Li, Dong; Yun, Jijun; Guo, Xiaobin; Wu, Kai; Zhang, Xu; Wang, Yupei; Zuo, Yalu; Gao, Meizhen; Xi, Li
Abstract: Perpendicular magnetic anisotropy (PMA) and spin–orbit torques (SOTs) are studied in a perpendicularly magnetized ultrathin Co film sandwiched between heavy metal Pt and Ta with an interfacial decoration performed by inserting a 3d transition metal Cr layer with a thickness of 2 nm between the Co and Ta. A significant enhancement of the perpendicular anisotropy field ( Oe) is established and estimated by measuring the extraordinary Hall resistance due to the Cr interfacial decoration. The improved antidamping-like field of ∼18.59 × 10 −6 Oe/(A·cm −2 ) reveals a large effective spin Hall angle of Pt/Co/Cr/Ta ∼0.41, which is caused by employing the dissimilar metals, Pt and Ta, with spin Hall angles of opposite sign and an additional interfacial spin–orbit coupling effect related to the Cr insertion. Thus, SOT-induced magnetization switching was achieved under a relatively small critical current density of the order of 10 6 A/cm 2 owing to the improved SOTs in the Pt/Co/Cr/Ta system. Our results indicate that the PMA and SOTs in Pt/Co/Cr/Ta structures can be enhanced via a Cr interfacial decoration.